2017
DOI: 10.1002/jsfa.8483
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinium meridionale Swartz extracts and their addition in beef burgers as antioxidant ingredient

Abstract: Mortiño extracts with high TPC can be obtained by PLE. Both mortiño and its PLE extract are able to control lipid oxidation of beef burgers, but the extract is preferred from the color quality point of view. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The 83,976.25 mg GAE/kg of TPC achieved in the CBE and elaborated in the present study is lower than that reported by Quintero-Quiroz et al [ 20 ] in a freeze-dried extract made from this fruit (139,290 mg GAE/kg). The extracts elaborated from this fruit by López-Padilla et al [ 21 ] by ultrasound-assisted extraction and pressurized liquid extraction had TPC contents between 71.70 ± 6.7 mg GAE/kg and 9.26 ± 2.52 mg GAE/kg. Different and fundamental aspects have to be considered to explain these differences.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The 83,976.25 mg GAE/kg of TPC achieved in the CBE and elaborated in the present study is lower than that reported by Quintero-Quiroz et al [ 20 ] in a freeze-dried extract made from this fruit (139,290 mg GAE/kg). The extracts elaborated from this fruit by López-Padilla et al [ 21 ] by ultrasound-assisted extraction and pressurized liquid extraction had TPC contents between 71.70 ± 6.7 mg GAE/kg and 9.26 ± 2.52 mg GAE/kg. Different and fundamental aspects have to be considered to explain these differences.…”
Section: Discussionmentioning
confidence: 91%
“…In a way, our results are not surprising in agreement with Lorenzo et al [ 16 ], who recently published a review indicating the use of berry extracts as natural antioxidants in meat products. In the same line, López-Padilla et al [ 21 ] also reported that CB is being valorised as raw material for the recovery of rich antioxidants with the application as natural additives in meat products. The DPPH, IC 50 , ABTS ● + , ORAC, and FRAP values obtained for the CBE can be attributed to the presence of phenolics compounds with high antioxidant and radical scavenging activity [ 18 , 19 ], especially anthocyanins (e.g., monoglucosides of cyanidin and delphinidin), hydroxycinnamic acids (e.g., coumaric acid), and flavanols (e.g., quercetin derivatives).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, a great amount of polyphenols was found in the aqueous extracts, which could be responsible of the mentioned activity, with the highest content in grape fruit extract. Another example of application of PLE extracts was given by López-Padilla et al [40]. They studied the antioxidant activity of some PLE extracts from Vaccinium meridionale Swartz in order to add it in beef burgers, obtaining an optimum phenol-rich extract using a mixture of ethanol:water (1:1), 200 °C and only 15 min static extraction time.…”
Section: Plants As a Source Of Bioactivesmentioning
confidence: 99%